Designing A Leadership Training Program For School Principals To Improve The Quality Of School Management - Usman H Miri; Purwanto Purwanto; Khuriyah Khuriyah; Islah Gusmian (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This article discusses designing a leadership training program for school principals to improve school management amidst the changing dynamics of education. This research uses qualitative methods by collecting data through observation, documentation and interviews from foundation leaders, school principals and school representatives in the three schools that are the research objects. The research results show that developing school principal competencies can be carried out with a comprehensive approach involving training strategies, skill building, and conceptual understanding. The quality of school management as reflected in school leadership greatly influences school performance. School principals have an important role in improving educational standards, but not all have adequate leadership abilities. With a designed program, school principals can become leaders who are adaptive to changes and challenges in the world of education. This article also emphasizes the importance of improving school management through effective leadership, with the hope of creating a learning environment that motivates staff and encourages innovation to improve the quality of education. Thus, this article provides valuable insights for educational institutions to understand the key role of school principals in improving the quality of school management.